Analisis Pengaruh Self Service Technology Terhadap Kualitas Pelayanan Restoran, Studi kasus di McDonald’s TB Simatupang, Jakarta - Shinta Teviningrum; Fawahidah Urfa (Universitas Nusantara PGRI Kediri, 2021)
The rapid development of technology has entered various aspects of today's society. Technology is considered to be able to answer the needs of urban people who have high mobility in a limited time. One of the technologies used is the self-ordering kiosk at McDonald's Fast Food Restaurants. This study aims to determine the effect of the dimensions of self service technology which include functionality, enjoyment, security/privacy, design, assurance, convenience, and customization partially (individually) or simultaneously (together) on service quality. From the multiple linear regression test, the result is that self-ordering kiosk technology has no effect on service quality.